Linking soil methane fluxes and diversity of methane-cycling microbial communities in response to land-use change in tropical and temperate forests - Alvarez, Dasiel Obregón (2021)
Methane (CH4) constitutes the second most important greenhouse gas after CO2, and accounts for up to 2030% of global warming. Significant accumulation of CH4 in the atmosphere (~44%) is associated with land-use change. In soil, CH4 production and oxidation rates are intrinsically linked, and driven by methanogens (archaea) and methanotrophs (bacteria) which are, at the same time, shaped by edaphic and environmental conditions. This arises as a relevant issue due to the increasing intensification of agriculture, particularly in the context of climate change. This thesis focused on the characterization of methanogenic and methanotrophic communities and their response to land-use change in tropical and temperate forests. The thesis consists of three chapters presented in scientific manuscript format. The study in Chapter 1 was addressing the impact of forest-to-pasture conversion on CH4-cycling communities in Rondonia, Brazil, through metagenomic sequencing and high-resolution taxonomic and functional analysis, exploring biotic and abiotic factors influencing these microbial groups. Chapter 2 delves deeper into the study of forest-to-pasture conversion in another region of the Amazon Basin (Pará, Brazil) to identify the abiotic drivers of methanogenic and methanotrophic communities in forest and pasture soils. In this chapter, CH4 fluxes and edaphic parameters were measured in two seasons (wet and dry), two soil types (sandy and clayey) and four soil depths. The analyses included ~280 samples of 16S rRNA sequencing, the isotopic composition of CH4 samples, and soil physical and chemical properties. The study in Chapter 3, performed in Ontario, Canada, aims to compare the structure and activity of methanogens and methanotrophs in five riparian buffer systems with contrasting plant coverage in an agricultural landscape. Soils samples were collected during CH4 emissions hotspots, and DNA and cDNA samples were sequenced using nPCR-amplicons from pmoA gene (methanotrophs) and archaeal 16S rRNA (methanogens). Overall, our results provide strong evidence of the transformation of CH4-cycling communities due to land-use change, and identifies key abiotic drivers behind these microbial changes